Cluster-Based Assessment to Improve Student Social Skill and Competence at SMA Muhammadiyah 10 Surabaya - Alif Putra Lestari; Ahmad Saikhu; Bejo Apriyanto; M. Rizqon Al Musafiri; Salim Bahrisy (International Journal of Geography, Social, and Multicultural Education, 2026)
Assessment of social skills and competencies is still often carried out conventionally and partially, thus lacking a comprehensive and objective picture. Cluster-based assessment is an alternative in developing student assessment models. This approach is appropriate and aligned with 21st-century education. This study used a qualitative method with a case study approach and formative evaluation to evaluate the effect of social cluster-based assessment in the form of a project on improving students' social skills and competencies. The subjects were 11th-grade students at SMA Muhammadiyah 10 Surabaya taking geography, sociology, and economics. The results showed that project-based assessment significantly improved students' skills and competencies. Students produced dioramas that were appropriate to the material, creative, and integrated with several subjects. Students also collaborated, communicated, tolerated, and respected each other during the project process. Teachers and students responded positively to the assessment implementation, adding motivation and making it enjoyable. This assessment model can be implemented and developed for better learning.